Social support, stress, and burnout among Icelandic police officers - Röskva Vigfúsdóttir 1992- (2017)
Previous studies indicate that police work is stressful and that it can lead to job burnout, particularly among those that have lower levels of social support. The aim of the current research was to identify levels of distress and burnout and to explore the relationship between social support, stress and burnout among Icelandic police officers. The sample consisted of 93 police officers in Iceland, 81.7% male and 18.3% female. Social support from co-workers and family and friends, stress and burnout were assessed with online questionnaires. Results indicated that 26.9% of participants reported high levels of stress and around 30% of participants had symptoms of burnout. Pearson correlational analysis revealed that those with higher levels of social support from co-workers reported both less stress and burnout while social support from family and friends was only associated with lower stress levels. Mediational analyses showed that the relationship between social support from co-workers and burnout was mediated by the impact of social support from co-workers in reducing stress. Future studies should design and test interventions aimed at increasing social support, particularly in the workplace, as that may reduce stress which in turn would reduce the likelihood that burnout symptoms will develop. Keywords: police officers, social support, stress, burnout Fyrri rannsóknir gefa til kynna að lögreglustarfið sé streituvaldandi og það geti leitt til kulnunar í starfi, sérstaklega á meðal þeirra sem hafa minni félagslegan stuðning. Markmið þessarar rannsóknar var að bera kennsl á umfang streitu og kulnunar og að kanna sambandið á milli félagslegs stuðnings, streitu og kulnunar á meðal íslenskra lögregluþjóna. Úrtak rannsóknarinnar samanstóð af 93 lögregluþjónum, 81,7% körlum og 18,3% konum. Félagslegur stuðningur frá samstarfsfélögum og fjölskyldu og vinum, streita og kulnun voru metin með rafrænum sjálfsmatsspurningalistum. Niðurstöður leiddu í ljós að 26,9% þátttakenda greindu frá mikilli streitu og um 30% ...